Fermented and nonfermented soy foods and the risk of breast cancer in a Japanese population‐based cohort study - Shirabe, Ritsuko (Cancer Med, 2020)
BACKGROUND: Although preclinical studies suggest that fermented soy foods may have a protective effect against breast cancer, no prospective cohort studies have examined this association. OBJECTIVE: Our study examined the association between fermented and nonfermented soy food intake and breast cancer risk using a population‐based prospective cohort study in Japan. METHODS: We included a total of 47,614 women aged 45–74 years in an analysis of the Japan Public Health Center‐based Prospective Study (JPHC Study). A validated food frequency questionnaire (FFQ) was used for the assessment of dietary intake. Breast cancer incidence was analyzed by multivariate Cox proportional hazards regression models. RESULTS: During an average of 15.5 years of follow‐up, 825 breast cancer cases were newly identified. We found no association of intake of soy foods with breast cancer risk, regardless of fermentation, with multivariate hazard ratios (HRs) and 95% confidence intervals (CIs) for the highest quartiles of fermented and nonfermented soy food intake of 0.94 (0.67, 1.32) and 1.15 (0.85, 1.57) compared with the lowest quartile (p for trend = 0.305 and 0.393). Unlike nonfermented soy, higher intake of fermented soy foods was associated with a significant decrease in the risk of nonlocalized breast cancer. The HR and 95% CI in the highest compared to lowest intake category of fermented soy foods was 0.53 (0.28, 0.99) versus nonfermented soy foods 0.85 (0.51, 1.42) (p for trend = 0.026 and 0.797). CONCLUSIONS: Our analyses showed that fermented soy foods had no association with overall breast cancer but may be associated with decreased risk of nonlocalized breast cancer.